Analysis of The Determinants of Regional Government Loans District/City In Indonesia 2017 - 2021 - Ratnasari, Dewi Pamungkas; Suhendro, Saring; Alvia, Liza (Basecamp Economics PubMed, 2024)
The formation of regions aims to accelerate the realization of community welfare and reduce disparities between regions, by carrying out constant and quality development. Until 2021, data from PT. SMI only 5.35% of regional governments that are eligible for loans utilize loans, while data from the Ministry of Finance's DJPK, regions that take loans are only 17.52%. This shows that many regional governments do not take advantage of regional loans to carry out their obligations to improve welfare in their regions. This study aims to analyze the effect of regional original income, regional financial capacity, regional fiscal capacity, and capital expenditure on regional loans. This study was conducted on all district/city governments in Indonesia that took out regional loans in the 2017-2021 period. Data analysis uses panel data regression with an approach Random Effect Model (REM). The results of the study indicate that increasing local revenue and high levels of regional financial capacity do not necessarily encourage district/city governments to undertake regional loans. Meanwhile, regional fiscal capacity and capital expenditures influence local governments to undertake regional loans.